The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1159/000047957
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Cardiovascular Autonomic Function Study in Mild Guillain-Barré Syndrome

Abstract: To identify subclinical autonomic dysfunction in mild Guillain-Barré syndrome (GBS), a set of autonomic function tests was serially performed for up to 6 months in 5 GBS patients with mild disability at the nadir. Parasympathetic autonomic function tests consisted of Valsalva ratio and R-R interval variation during rest and deep breathing. Sympathetic autonomic function was evaluated by blood pressure responses to sustained handgrip, hand immersion in ice water, and active standing. The results showed that abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…Both features may be present even in the same patient. Longitudinal studies of cardiovascular reflex tests have shown that up to 90 % of patients are affected by autonomic failure and that the recovery of autonomic dysfunction parallels the improvement of motor function [16,29]. Power spectrum analysis of heart rate variability indicated that the sympathovagal balance was shifted towards sympathetic function during the acute stages of the disease [8].…”
Section: Guillain-barré Syndrome (Gbs)mentioning
confidence: 99%
“…Both features may be present even in the same patient. Longitudinal studies of cardiovascular reflex tests have shown that up to 90 % of patients are affected by autonomic failure and that the recovery of autonomic dysfunction parallels the improvement of motor function [16,29]. Power spectrum analysis of heart rate variability indicated that the sympathovagal balance was shifted towards sympathetic function during the acute stages of the disease [8].…”
Section: Guillain-barré Syndrome (Gbs)mentioning
confidence: 99%
“…[4][5][6] Autonomic function abnormalities of our patients with FS were highest during the acute stage of neuropathy and improved gradually after 1-3 months. Therefore, autonomic dysfunction in FS is transient and resolves gradually over time, as is seen in GBS.…”
Section: Manifestations Of Autonomic Dysfunction In Patients Withmentioning
confidence: 71%
“…6 The autonomic function tests were the Valsalva ratio, RRIV during rest and deep breathing, and BP responses to sustained handgrip (SH) and active standing. During the Valsalva ratio test, the patient was asked to blow into a mouthpiece and maintain a pressure of about 40 mm Hg for 15 seconds.…”
Section: Autonomic Function Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has helped characterize particularly the parasympathetic nervous function in healthy subjects and patients with different clinical conditions, such as diabetes mellitus (3,4,9,16,20), systemic arterial hypertension (47), coronary disease (48), heart failure (1, 36), chronic Chagas' disease (2,17,21,22,30,31,34), neurological diseases (7,28,49), and renal failure (15,39), among many others. This approach has helped characterize particularly the parasympathetic nervous function in healthy subjects and patients with different clinical conditions, such as diabetes mellitus (3,4,9,16,20), systemic arterial hypertension (47), coronary disease (48), heart failure (1, 36), chronic Chagas' disease (2,17,21,22,30,31,34), neurological diseases (7,28,49), and renal failure (15,39), among many others.…”
Section: Clinical Physiology Applicationmentioning
confidence: 99%